Aluminum complexes based on pyridine substituted alcohols: synthesis, structure, and catalytic application in ROP1. Issue 26 (14th July 2015) - Kireenko, Marina M.; Kuchuk, Ekaterina A.; Zaitsev, Kirill V.; Tafeenko, Viktor A.; Oprunenko, Yuri F.; Churakov, Andrei V.; Lermontova, Elmira Kh.; Zaitseva, Galina S.; Karlov, Sergey S.
<x xml:space="preserve">Abstract</x> 2, 6-Bis(hydroxyalkyl)pyridines were used in the synthesis of Al complexes. The structure of the ligand determines the complex nature. Compounds were used as initiators of lactone ROP.